(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the changes in the degree of polarization of the flux reflected from crystals and solid bodies with high optical thickness () when illuminated by polarized radiation. It is shown that when the crystals are illuminated by an unpolarized flux, neutral points exist in the angular characteristics of the flux reflected from the crystals. The similar and distinctive features of linearly and circularly polarized radiation fluxes are analyzed.c